A “Wake-Up Call” for EFL Students: Exploring the Metacognitive Learning Strategy in the Professional Listening Course - Anaktototy, Karolis (REiLA : Journal of Research and Innovation in Language, 2022)
Compared to the cognitive strategies to solve students’ problems in English listening, studies on metacognitive strategies seem to be underexplored in Eastern Indonesian context. In order to contribute to this research gap, this study conducted an investigation on university students' awareness of metacognitive strategies. This mixed-method study used quantitative data from a questionnaire adopted from the Metacognitive Awareness Listening Questionnaire (MALQ). 178 English Education students (19-21 years old) at Pattimura University completed the questionnaire, and eight students were randomly selected to be interviewed to obtain qualitative data regarding their individual metacognitive strategies for planning, monitoring and evaluating their listening activities. The findings reveal more than 60% of the participants agree that they have a plan for their listening activities, can maintain focus during the activities, and evaluate how they performed. Qualitative data supported that the students do have a plan and monitor their learning process, as they can provide specific strategies of how they plan (e.g., taking notes, making sure that the room is suitable for listening tasks) and monitor (e.g., paying attention to keywords, using context to decipher audio’s meaning if they encounter unfamiliar words) their learning process. However, the students seem to be unable to explain or define precisely what metacognitive strategy is, indicating their lack of learning the self-reflection process. These results demonstrated a need for more explicit instruction of metacognitive strategies to improve the students’ learning process, which will be especially beneficial for the university's uniquely high-stakes course of Professional Listening.